Peculiarities of Nickname Semantics in Veliuona Region: Primary Nicknames - Mickienė, Ilona; Baranauskienė, Rita (Respectus Philologicus, 2016)
The article focuses on the analysis of 425 primary nicknames recorded in Veliuona vicinity aiming to deduce their most common semantic features. The semantics of nicknames, their origins and common connotations are examined in greater detail. When analysing nickname semantics, the motives for nickname attribution and dictionary definitions are taken into account. Examining nicknames semantically, first of all, the basis for nickname derivation is determined, i.e., a proper word meaning the name of an individual object or an appellative meaning, the generalised name of an object. Further on, the nicknames are classified into smaller semantic groups. The research has disclosed that the greater group of nicknames is comprised of appellatives, which stand for a generalised name of an object (339 nicknames, 79.8 per cent), while nicknames made of proper names constitute the smaller group (86 nicknames, 20.2 per cent). The analysis of nickname semantics has detected semantic groups, which reflect the system of forming primary nicknames in Veliuona vicinity. The semantic classification of primary nicknames proposed in the article is in principle new with reference to Vanagas classification scheme of hydronym semantics; therefore, it is open for discussion, improvement and complementation.